2010
DOI: 10.1371/journal.pbio.1000297
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt Pathway Controls Cell Death Engulfment, Spindle Orientation, and Migration through CED-10/Rac

Abstract: Specificity in Wnt-mediated developmental processes, such as directional cell cleavage, migration, and engulfment of dead cells in C. elegans, arises from the use of distinct Wnt pathway signalling modules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
94
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 48 publications
(69 reference statements)
1
94
1
3
Order By: Relevance
“…Its simplicity, the stereotyped cell lineage, and cell movements pattern, together with its transparency, make this animal an ideal model for studying development. Genetic studies, in combination with 4D microscopy analyses, have shown that CED‐10/Rac is required for proper rotation of the mitotic spindle of some early blastomeres in the C. elegans embryo, named EMS − the endoderm and mesoderm precursor – and ABar − whose descendants form part of the pharynx − 15, 16. These mitotic spindle orientations are induced by cell signaling, from blastomeres derived from the posterior cell at the two‐cell stage embryo − termed P1 −, that triggers actin cytoskeletal reorganizations in the target cells.…”
Section: Rac/rho Small Gtpases Mediate Spindle Orientation and Cell Dmentioning
confidence: 99%
See 4 more Smart Citations
“…Its simplicity, the stereotyped cell lineage, and cell movements pattern, together with its transparency, make this animal an ideal model for studying development. Genetic studies, in combination with 4D microscopy analyses, have shown that CED‐10/Rac is required for proper rotation of the mitotic spindle of some early blastomeres in the C. elegans embryo, named EMS − the endoderm and mesoderm precursor – and ABar − whose descendants form part of the pharynx − 15, 16. These mitotic spindle orientations are induced by cell signaling, from blastomeres derived from the posterior cell at the two‐cell stage embryo − termed P1 −, that triggers actin cytoskeletal reorganizations in the target cells.…”
Section: Rac/rho Small Gtpases Mediate Spindle Orientation and Cell Dmentioning
confidence: 99%
“…1). In addition to Wnt signaling, other pathways acting upstream of CED‐10/Rac, such as those described in the engulfment of the apoptotic corpses, may provide a minor contribution to embryonic cell spindle orientation 16, 18 (Fig. 1).…”
Section: Rac/rho Small Gtpases Mediate Spindle Orientation and Cell Dmentioning
confidence: 99%
See 3 more Smart Citations